Modelling innovation support systems for development - Vaz, Eric (2014)
The present article offers a concise theoretical conceptualization on the contribution of innovation to regional development. These concepts are closely related to geographical proximity, knowledge diffusion and filters, and clustering. Institutional innovation profiles and regional patterns of innovation are two mutually linked, novel conceptual elements in this article. Next to a theoretical framing, the paper offers also a new methodology to analyse institutional innovation profiles. Our case study addresses three Portuguese regions and their institutions, included in a web-based inventory of innovation agencies which offered the foundation for an extensive data base. This data set was analyzed by means of a recently developed Principal Coordinates Analysis followed by a Logistic Biplot approach (leading to a Voronoi mapping) to design a systemic typology of innovation structures where each institution is individually represented. There appears to be a significant difference in the regional innovation patterns resulting from the diverse institutional innovation profiles concerned. These profiles appear to be region-specific. Our conclusion highlights the main advantages in the use of the method used for policy-makers and business companies.